Penguatan Industrialisasi di Bidang Peternakan Guna Meningkatkan Produktivitas dan Investasi di Kabupaten dan Kota - Ikke Adelia Amanfa; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to strengthen industrialization in the livestock sector to increase productivity and investment at the district and city levels. The use of modern technologies, such as digital livestock management systems, sensor-based animal health monitoring, and automated feeding systems, has increased in recent years in response to the need for efficiency and improved production outcomes. Data were collected from various livestock units, ranging from small-scale to large-scale farms, through surveys and observations over a two-year period. The analysis results show a significant positive relationship between the level of investment in livestock technology and productivity improvements, both in terms of livestock population growth and production outputs (meat, milk, eggs). Higher investment in technology tends to result in better operational efficiency, lower animal mortality rates, and improved product quality. These findings indicate that accelerating the adoption of technology in the livestock industry can be an effective strategy to enhance the competitiveness and sustainability of the national livestock sector.